Speech Acts in Text Dialogues: An Analysis of English Textbook Merdeka Belajar for Junior High School - Fitriani, Fitriani; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to investigate the types of speech acts and their functions contained in the dialogues of the English textbook titled